Assessing Self-Reliance among Generation Z in Junior High School: An Analysis Using Rasch Model - Isma Aziz Fakhrudin; Budi Utami; Nurma Yunita Indriyanti; Annisa Nur Khasanah; Riezky Maya Probosari; Supurwoko; Ahyana Rosyada; Eva Permatasari (Jurnal Penelitian Pendidikan IPA, 2024)
Generation Z in Indonesia is facing conditions where there are a lot of challenges such as violences in school, career, and sustainibility development. Therefore, Indonesia has developed an Independent Curriculum to acomodate and promote student’s self-reliance as a part of Pancasila Profile dimensions as a preventive action to face 21st century challenges. This research aims to assess student’s self-reliance among generation Z in Junior High School. This study is quantitative research explaining the quality of instrument and classifying student’s abilities based on questionnaire analyzed by using Rasch Model. The sample used in this research consist of 104 students from Junior High School that have been given a P5 program and required to be tested using 26 test items. The result of self-relliance quistionnaire is analyzed using the rasch model. The findings explained that students score and mostly get the lowest score in gender or demographic analysis. In conclusion, student’s self-reliance among generation Z is still unequal and low neither in gender or demographic. Furthermore, school should train student’s self-reliance intensively to prepare students facing future challenges.